(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. The research was an attempt to explore the potential impact of allicin on lipid peroxidation and oxidative stress in rats diagnosed with chronic kidney disease (CKD), and to determine its underlying mechanism. Methods. Sixty rats were randomly divided into sham-operated, modelling, and allicin low, medium, and high dose groups. The histopathological structure of the kidney was observed in each group. Biochemical measurements were conducted to assess kidney function, including serum creatinine (Scr) and blood urea nitrogen (BUN), and 24-hour urine protein quantification. Levels of malondialdehyde (MDA), superoxide dismutase (SOD), reactive oxidative species (ROS), and reduced glutathione (GSH) in kidney tissue were measured, and mitogen-activated protein kinase (MAPK) and NF (nuclear factor) -κB protein levels were detected by western blotting. Results. They showed that allicin improved the pathological structure of renal tissue and protected renal function by reducing oxidative stress and lipid peroxidation via targeting the ROS/ MAPK/NF-κB pathway. Allicin increased SOD and GSH levels, while decreasing Scr, MDA, ROS, BUN, and the amount of protein excreted in urine over a 24-hour in medium and high dose groups. MAPK and NF-κB protein levels in medium and high dose allicin groups were lower than the modelling group. Conclusion. Based on the results, it can be inferred that allicin may safeguard renal function in rats with CKD and has the potential to serve as a treatment for kidney ailments. DOI: 10.52547/ijkd.7496